PENGARUH MODEL HIDROPONIK DAN JENIS PUPUK ORGANIK TERHADAP PERTUMBUHAN TANAMAN SELEDRI (Apium Graveolens L) - Yuni Dwi Indarwati; Asad Syamsul Arifin; Mistianah Mistianah (Edubiotik : Jurnal Pendidikan, Biologi dan Terapan, 2016)
Hydroponics was derived from the Greek words hydro that means water and ponos which means power. Hydroponics was also known as soilless culture or cultivation of plants without soil. So hydroponic means the plants mindculture utilizing water or without using soil as a soilless growing media. But there were also hydroponics that using soil, chaff, and sand or gravel. Hydroponics system was also applied to the vegetable crops and fruits. The vegetable crops that had been developed with hydroponic system were cabbage, lettuced, kale and celedry. The hydroponic models that used in this research was wick hidroponic models and vertical pipa paralon culture. Each of hydroponic models has its own short coming and advantages. Other factors that also determine the plants growth was fertilizer (nutrient). The nutrient that used in this research were tea waste, fertilizers coffee grounds. The purpose of this study was to investigate the effect of hydroponic models and nutrients to the celedrys growth rate. The research was quantitative research. Research conducted in the Ngumpul village in Ponorogo. Research held three times and analyzed using ANOVA test, then analyzed with Duncan test.